Umbilical Cord Immunoglobulins and Fetal Maturity: Neonates in a Guatemalan Indian Village - Mata Jiménez, Leonardo (1977)
During a 9-year prospectivestudy in a Mayan Indian village (1), umbilical cord blood was collected by untrained midwivesfrom most newborns. Specimens mixed with maternal blood were screened according to their ratios of immunoglobulinM (IgM) to immunoglobulinA (lgA) (2). All remaining specimens with levels of IgA equal to or greater than 0.10 mg/rnl were also excluded. Of the 401 original specimens, 250 were used in the study. Analysis of variance revealed no clear pattern associating IgM values with birth weight or gestational age (Table 2,3). Highest values were noted in infants of 35 to 36 weeks' gestation. Comparison of IgM values with combined birth weight and gestational age (fetal maturity) showed that the highest values were in three infants classifiedas pretenn, moderate low birthweight (Table 4). Analysis of IgG values, on the other hand, revealed a clear pattern; mean IgG was significantly correlated with birth weight, increasing until birth weight reached 3,000 g. The correlation with gestational age was even higher, lasting until 41-42 weeks' gestation. The lowest IgG